Concept Development of a Cessna 150 Digital Twin using Multi-Agent-Systems - Erik Suer (2021)
In order to digitize and improve operational procedures with interacting digital twins in aviation industry, new approaches are necessary. One approach is the use of multiagent systems. The objective of this thesis is to develop a concept for a digital twin using a multi-agent system, which models a Cessna 150 as well as its pilot and the air traffic controller. The first implementation of this system is based on the "MARS" framework. The MARS group represents all “Multi-Agent Research and Simulation” activities at the University of Applied Sciences Hamburg at the Department of Computer Science. The developed and implemented concept demonstrates a first simulation approach, which aims to model the flight operation from preflight check to takeoff. This concept and its first implementation are presented and evaluated. Afterwards, with exploring the potential of multi-agent systems, further recommendations for the application along the flight operation stages are done. The result of this thesis offers a better understanding of multi-agent system in aviation industry and acts as a first foundation for future research with MARS in this area.
Keywords: Digital Twin; (Multi-) Agent-System; Industry 4.0; Cessna; Aerospace Engineering